Martes Pinel 1792 - Jo, Yeong-Seok; Baccus, John T.; Koprowski, John L. (Zenodo, 2018)
Genus Martes Pinel, 1792 The genera Martes, Meles, and Mustela, represent the Subfamily Mustelinae in Korea. Analyses of mtDNA indicated a paraphyletic status for the Genus Martes, with M. pennanti being closer to Gulo gulo than other species of Martes (Stone & Cook 2002). Three Subgenera, Martes, Charronia, and Pekania, are recognized (Wozencraft 2005). Three species of Martes inhabit the Korean Peninsula; M. flavigula classified in the Subgenus Charronia and the other two species in the Subgenus Martes. Published as part of Jo, Yeong-Seok, Baccus, John T. & Koprowski, John L., 2018, Mammals of Korea: a review of their taxonomy, distribution and conservation status, pp. 1-216 in Zootaxa 4522 (1) on page 68, DOI:10.11646/zootaxa.4522.1.1, http://zenodo.org/record/2610198